Application Of Crashing Method On Sutt Construction Project 150 Kv Kolaka - Pomalaa Switching - PT Antam Pomalaa Customer - Rachim, Fatmawaty; Frans Ryanto Hasudungan Tampubolon; Herwina Rahayu Putri; Andi Butsainah Tumaadir (Program Studi Teknik Sipil, Fakultas Teknik, Universitas Islam Lamongan, 2025)
Construction projects often experience delays that can result in a fine of 1/1000 of the contract value according to Presidential Regulation No. 54/2010. To overcome this, the crashing program method can be applied to accelerate the project duration by identifying and compressing the critical path. The case study on the 150 kV Kolaka - Pomalaa Switching - PT Antam Pomalaa SUTT Construction Project which experienced delays, analyzed the need for additional time, equipment and labor. With an initial contract duration of 300 calendar days, the implementation of the crashing program focused on four priority segments of work (TIP 40-54, TIP 01-11, TIP 23-40, and TIP 11-23). The results of the analysis showed that the application of the crashing program method successfully optimized the project completion duration to 263 days, allowing the project to return to the contract schedule and avoid potential fines.